2021
DOI: 10.1002/jssc.202100348
|View full text |Cite
|
Sign up to set email alerts
|

Method validation and residue analysis of methoxyfenozide and metaflumizone in Chinese broccoli under field conditions by liquid chromatography with tandem mass spectrometry

Abstract: Methoxyfenozide and metaflumizone are insecticides used on Chinese broccoli to prevent insects and increase yield. However, the residues are potentially harmful to the environment and consumers. In this study, the quick, easy, cheap, effective, rugged, safe method with high-performance liquid chromatography with tandem mass spectrometry was modified and validated for determination of methoxyfenozide and metaflumizone in Chinese broccoli. The clean-up efficiency of different sorbents including C 18 , primary se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Acetonitrile and acetone have generally been used as extraction solvents for agricultural products; thus, it has been reported that these solvents have high extraction efficiency in the process of extracting methoxyfenozide from agricultural products [27,28]. However, it is reported that pymetrozine is a highly polar pesticide (log Pow: −0.18, water solubility: 0.29 g/L), and it is necessary to adjust the pH by adding a weakly basic buffer solution to suppress ionization to achieve a high extraction efficiency [29,30].…”
Section: Analytical Methods Validationmentioning
confidence: 99%
“…Acetonitrile and acetone have generally been used as extraction solvents for agricultural products; thus, it has been reported that these solvents have high extraction efficiency in the process of extracting methoxyfenozide from agricultural products [27,28]. However, it is reported that pymetrozine is a highly polar pesticide (log Pow: −0.18, water solubility: 0.29 g/L), and it is necessary to adjust the pH by adding a weakly basic buffer solution to suppress ionization to achieve a high extraction efficiency [29,30].…”
Section: Analytical Methods Validationmentioning
confidence: 99%
“…The vapor pressure, partition coefficient, and water solubility of methoxyfenozide were < 1.33 × 10 −5 Pa, log Pow 3.72 ± 0.04 at 24.7 ± 1.4 ℃ (pH 7), and 3.3 mg/L at 20 ± 0.5 ℃ (pH 7), and 3.3 mg/L methoxyfenozide, 2003). The methoxyfenozide dissipation rates of litchi and longan were slower than those previously reported for pak choi (initial concentrations = 2.8 mg kg −1 , half-life = 3.9 days) (Tang et al 2021 ), spinach (initial concentrations = 1.2–3.8 mg kg −1 , half-life = 1.4–3.0 days) (Feng et al 2022 ), Chinese cabbage (initial concentrations = 1.12–1.33 mg kg −1 , half-life = 1.2 days) (Wang et al 2022 ), Chinese broccoli (initial concentrations = 0.27–1.73 mg kg −1 , half-life = 1.0–5.1 days) (Bi et al 2021 ), and cauliflower (initial concentrations = 2.5–3.5 mg kg −1 , half-life = 0.14–4.38 days) (Sun et al 2019a , b ). The above reports include residue levels observed in vegetables and pesticide degradation during harvesting is generally faster due to the short growth cycle of vegetables.…”
Section: Resultsmentioning
confidence: 99%
“…Two different modified reverse phase columns; Acquity T3 and Xselect high-strength silica (HSS) pentafluorophenyl (PFP) were used in the present study considering the less column maintenance, wider pH and solvent compatibility, and longer lifetime than the previously reported columns [9][10][11][12][13][14][15]. Two methods (M1 and M2) were validated against the two analytical columns with acceptable chromatographic retention and separation [16][17][18][19][20]. Importantly, the compatibility of the test methods used for the analysis of Glyphosate in HW has not been adequately demonstrated in previous methods [21].…”
mentioning
confidence: 99%